Implementing the IB diploma programme : a practical manual for principals, IB coordinators, heads of department and teachers - Loo, Marc van.; Morley, Kevin (New York : Cambridge University Press, 2004)
A guide to the implementation of the International Baccalaureate Diploma Program that provides an introduction to the program and advice on teaching at diploma level; discusses authorization and the benefits and costs of the program; and includes case studies.
Adult
Keywords: Curriculum planning; International baccalaureate; Curriculum planning; International education